A review on the pharmacology of cariprazine and its role in the treatment of negative symptoms of schizophrenia - Selvan, Panneer; Devkare, Prashant; Shetty, Arthik; Dharmadhikari, Shruti; Khandhedia, Chintan; Mane, Amey; Mehta, Suyog; Andrade, Chittaranjan (Frontiers in Psychiatry, 2024)
Management of negative symptoms is one of the most challenging and important unmet needs of schizophrenia treatment. Negative symptoms together with positive symptoms result in significant psychosocial impairment and poor quality of life. Existing studies on atypical antipsychotics reported limited treatment adherence due to higher prevalence of treatment-emergent adverse events, such as diabetes, weight gain, hyperlipidemia, hyperprolactinemia and hypertension. A compound with greater affinity for dopamine D2/D3 receptors may improve negative symptoms, mood, and cognitive impairment associated with schizophrenia. In 2015, the US FDA has approved cariprazine, a partial D2/D3 agonist for treatment of schizophrenia, mania or mixed episodes. Midlands and Lancashire Commissioning Support Unit, UK (2019) has particularly suggested cariprazine for the treatment of predominant negative symptoms of schizophrenia. India’s Central Drugs Standard Control Organization (CDSCO) has approved cariprazine in 2021 for the treatment of schizophrenia, manic or mixed episodes associated with bipolar I disorder. A ten-fold greater affinity for D3 receptors and partial agonism to serotonin receptors, along with longer half-life make cariprazine distinct when compared with other atypical antipsychotics. Cariprazine is also reported to have fewer incidents of metabolic and hormonal adverse events, and has been shown to provide better relapse prevention. Recent evidence indicates promising effect of cariprazine in ameliorating negative symptoms as well as psychotic symptoms in patients with schizophrenia. In addition, improved adherence to treatment (adjunctive/monotherapy) with cariprazine in patients having inadequate response to an ongoing antipsychotic treatment has also been clinically established. This review presents the evidence-based safety and efficacy of cariprazine for treatment of predominant negative symptoms of schizophrenia.